Methane emissions from digestate at an agricultural biogas plant. (September 2016) - Baldé, Hambaliou; VanderZaag, Andrew C.; Burtt, Stephen D.; Wagner-Riddle, Claudia; Crolla, Anna; Desjardins, Raymond L.; MacDonald, Douglas J.
Highlights: Emissions measured from digestate at a biogas plant using manure and co-substrates. Five months from June to October accounted for 76% of annual CH4 emissions. Annual CH4 emissions averaged 19 g CH4 m −3 d −1 and 0.27 g CH4 kg −1 VS d −1 in storage. Emissions of CH4 from the digestate storage was 12% of what the digester produced. Digestate management is important for reducing emissions from biogas plants. Abstract: Methane (CH4 ) emissions were measured over two years at an earthen storage containing digestate from a mesophilic biodigester in Ontario, Canada. The digester processed dairy manure and co-substrates from the food industry, and destroyed 62% of the influent volatile solids (VS). Annual average emissions were 19 g CH4 m −3 d −1 and 0.27 g CH4 kg −1 VS d −1 . About 76% of annual emissions occurred from June to October. Annual cumulative emissions from digestate corresponded to 12% of the CH4 produced within the digester. A key contributor to CH4 emissions was the sludge layer in storage, which contained as much VS as the annual discharge from the digester. These findings suggest that digestate management provides an opportunity to further enhance the benefits of biogas (i.e. reducing CH4 emissions compared to undigested liquid manure, and producing renewable energy). Potential best practices for future study include complete storage emptying, solid-liquid separation, and storage covering.